2018
DOI: 10.1016/j.schres.2018.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing social functioning in young people at Ultra High Risk (UHR) for psychosis: A pilot study of a novel strengths and mindfulness-based online social therapy

Abstract: MOMENTUM is engaging and safe. MOMENTUM appeared to engage the hypothesized mechanisms and showed promise as a new avenue to improve social functioning in UHR young people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 58 publications
6
99
0
Order By: Relevance
“…It can be deduced that the higher the levels of mindfulness, the lower the risk of conducting high-risk behaviors. The finding is in line with the results obtained from several previous studies in this field (5,14,15). A study conducted by Alvarez-Jimenez et al (14) showed that mindfulness-based therapy was effective in reducing high-risk behaviors and improving adolescent's performance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It can be deduced that the higher the levels of mindfulness, the lower the risk of conducting high-risk behaviors. The finding is in line with the results obtained from several previous studies in this field (5,14,15). A study conducted by Alvarez-Jimenez et al (14) showed that mindfulness-based therapy was effective in reducing high-risk behaviors and improving adolescent's performance.…”
Section: Discussionsupporting
confidence: 90%
“…The finding is in line with the results obtained from several previous studies in this field (5,14,15). A study conducted by Alvarez-Jimenez et al (14) showed that mindfulness-based therapy was effective in reducing high-risk behaviors and improving adolescent's performance. In another study, Khanna and Greeson (15) demonstrated that yoga and mindfulness as complementary therapies were effective in reducing high-risk behaviors, including addiction.…”
Section: Discussionsupporting
confidence: 90%
“…In this context, social functioning has been increasingly recognized as a treatment outcome for psychotherapy interventions, beyond symptomatic remission (Renner, Cuijpers, & Huibers, ; Tan, Lee, & Lee, ). Improvements in social functioning have been found to not only correlate positively with engagement in interventions (Alvarez‐Jimenez et al, ) but also with an enhanced quality of life (Bonnin et al, ). In addition, functional recovery allows individuals to return to societal roles, which in turn has been suggested to have the greatest impact on challenging stigma of mental illness (Corrigan, Morris, Michaels, Rafacz, & Rusch, ; London & Evans‐Lacko, ).…”
Section: Discussionmentioning
confidence: 99%
“…While the use of online social media‐based interventions is in its infancy, pioneering efforts indicate that these interventions are safe, engaging, and have the potential to improve clinical and social outcomes in both patients and their relatives. That said, online interventions have failed up to now to be adopted by mental health services.…”
Section: Online Social Network: Faulty Connections or False Dichotomy?mentioning
confidence: 99%